Electrocardiographic Gating and Cerebral Perfusion Computed Tomography Option-Set Prevalence and Utilization Data From 62 Institutions in the United States. Issue 2 (13th March 2023) - Rose, Sean D.; Lubner, Meghan G.; Heil, John; Greenwood, Gina M.; Szczykutowicz, Timothy P.
Abstract : Objectives: To provide the radiology community with data to address the question: "Compared with peer institutions, is my institution efficiently using its electrocardiographic (ECG) gating and cerebral perfusion-capable computed tomography (CT) scanners?" Methods: In this retrospective study, we analyze 6 months of scanner utilization data from 62 institutions (299 locations, 507 scanners) to identify scanners capable of performing ECG gating and perfusion CT studies. We report the number of ECG gating/perfusion–capable scanners and locations as a function of the total number of locations and scanners in each institution. We additionally regress the number of ECG-gated and perfusion examinations on (1) the number of locations/scanners capable of performing these examinations and (2) the fraction of the institution's CT examination volume that requires ECG gating or perfusion. We provide look-up tables so an institution can compare its ECG-gated/perfusion examination volume to other institutions with similar ECG-gated/perfusion examination fractions and capable scanners. Results: We detected an effect of both ECG-gating examination fraction and the number of ECG gating–capable scanners on ECG-gated examination volume ( χ 2 1 = 77.5 [ P < 0.001] and χ 2 1 = 64.2 [ P < 0.001], respectively). Similar results were obtained for perfusion examination fraction and perfusion-capable scanners as they relate to perfusion examination volume ( χ 2 1 = 51.6 [ P < 0.001] and χ 2 1 = 45.2 [ P < 0.001], respectively). The number of ECG gating/perfusion–capable scanners and locations within an institution were found to positively correlate with both the total number of locations and scanners within an institution ( P < 0.001 for all hypothesis tests). Conclusions: The study provides multi-institutional data on ECG gating and perfusion examination volumes that can be used to inform CT purchasing decisions.